Riches without wings - Thayer, Ellis Cheney (My University, 1891)
Introduction: In writing this oration it is the author’s purpose to set forth the general indestructibility and need of character and education. The word character as here used is nearly synonymous with reputation—but it is broader. It includes honesty, esteem and in fact all the attributes which are brought to mind in the phrase, a man of character. By education is meant as Webster says “properly to draw forth. It implies not so much the communication of knowledge as the discipline of the intellect, the establishment of principles, and the regulation of the heart.” Education and character as used in this sense are truly riches without wings. They may be lost but if a person does lose them how often is it due to the fact that his other riches have gone before. How often it is true that insanity is brought about by loss of property, or, if unsuccessful in business, a man will sometimes stoop to do things he would not think of before.
Citation: Thayer, Ellis Cheney. Riches without wings. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Capitalism; Riches; Education; Character; Theses; Manuscripts (documents)